Monitoring Mental Health: Legal and Ethical Considerations of Using Artificial Intelligence in Psychiatric Wards - Barry Solaiman (19160614) (2024)
Artificial intelligence (AI) is being tested and deployed in major hospitals to monitor patients, leading to improved health outcomes, lower costs, and time savings. This uptake is in its infancy, with new applications being considered. In this Article, the challenges of deploying AI in mental health wards are examined by reference to AI surveillance systems, suicide prediction and hospital administration. The examination highlights risks surrounding patient privacy, informed consent, and data considerations. Overall, these risks indicate that AI should only be used in a psychiatric ward after careful deliberation, caution, and ongoing reappraisal. Other Information Published in: American Journal of Law & Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/amj.2023.30